Ontologies and Methods of Qualitative Research in Urban Planning - Rabino, Giovanni (TeMA - Journal of Land Use, Mobility and Environment, 2014)
Qualitative research can produce vast amounts of data and uses analytical categories to describe and explain social phenomena; several software packages are designed for qualitative data analysis and enable a complex organization of data. The study tests the capacity of new technology to build a formal ontology from qualitative data, in urban planning.